A nation of a hundred million idiots"? a social history of Japanese television, 1953-1973 - Chun, Jayson Makoto (East Asia (New York, N.Y.), 2007)
In a comparatively short period, the television industry helped to reconstruct not only postwar Japanese popular culture, but also the Japanese social and political landscape. This book offers a history of Japanese television audiences and the popular media culture that television helped to spawn